Down-regulation of the microRNA processing enzyme Dicer is a prognostic factor in human colorectal cancer - Faggad, Areeg; Weichert, Wilko; Stenzinger, Albrecht (Histopathology, 2012)
Aims: MicroRNA deregulation is a key feature of cancer; however, the molecular mechanisms underlying deregulation are unknown. Dicer is a central enzyme in microRNA processing essential for production of mature microRNAs which, in turn, regulate gene expression post-transcription. The aim was to investigate whether Dicer expression in colorectal cancer correlates with conventional clinicopathological parameters and patient survival. Methods and results: Immunohistochemical staining for Dicer was performed on tissue microarrays of 331 samples from patients with primary colorectal carcinoma. A subset (19.6%) of colorectal carcinomas was negative for Dicer. Dicer protein expression was associated significantly and inversely with disease (WHO) stage (P = 0.029), tumour grade (P = 0.001), tumour stage (P = 0.022) and nodal metastasis (P = 0.004). Negative expression of Dicer correlated significantly with shortened overall survival (P = 0.007) and was independent of other prognostic factors in multivariate analysis (Cox regression: P = 0.035, hazard ratio=1.6; 95% confidence interval 1.034-2.513). Additionally, in univariate analysis, an association of Dicer expression with survival was observed in subsets of patients without metastasis (P = 0.026), older patients (P = 0.005) and patients with advanced tumour stage (P = 0.022). Conclusion: Dicer deregulation is linked significantly to adverse disease state and decreased overall survival in colorectal cancer. Our data suggest that reduced Dicer expression might contribute to tumour progression in colorectal cancer.